Screening asylum seekers in Denmark for torture using a structured questionnaire - Ebbe Munk-Andersen; Bettina Toftgaard; Jens Modvig (Torture)
The United Nations Committee against Torture recommends systematic torture screening throughout the asylum process.   The goal of this study is to evaluate the introduction of a structured questionnaire, coding for torture according to the definition from United Nations Convention Against Torture (UNCAT). This screening for torture is now an integrated part of the medical reception of newly arrived asylum seekers